Dollar a day, 10 cents a dance - Dunn, Geoffrey; Schwartz, Mark (Cinema Guild, 1984)
Presents a portrait of Filipino farm laborers who came to the U. S. in the 1920's and 1930's, expecting a more prosperous life-style. Voicing their recollections, these now elderly men reveal the poverty, and social and cultural difficulties they experienced.